Myxococcus xanthus mokA Encodes a Histidine Kinase-Response Regulator Hybrid Sensor Required for Development and Osmotic Tolerance - Kimura, Yoshio (American Society for Microbiology, 2001)
A gene, mokA, encoding a protein with similarities to histidine kinase-response regulator hybrid sensor, was cloned from a Myxococcus xanthus genomic library. The predicted mokA gene product was found to contain three domains: an amino-terminal input domain, a central transmitter domain, and a carboxy-terminal receiver domain. mokA mutants placed under starvation conditions exhibited reduced sporulation. Mutation of mokA also caused marked growth retardation at high osmolarity. These results indicated that M. xanthus MokA is likely a transmembrane sensor that is required for development and osmotic tolerance. The putative function of MokA is similar to that of the hybrid histidine kinase, DokA, of the eukaryotic slime mold Dictyostelium discoideum.